- #1

JoeAllen

- 5

- 1

I assumed three points for a triangle P1 = (a, c), P2 = (c, d), P3 = (b, e)

and of course:

a, b, c, d, e∈Z

Using the distance formula between each of the points and setting them equal:

\sqrt { (b - a)^2 + (e - d)^2 } = \sqrt { (c - a)^2 + (d - d)^2 } = \sqrt { (b - c)^2 + (e - d)^2 }(e+d)

(e+d)

c

c

c(c - 2b) = a(a - 2b)

Thus, for this to be true, a = c. But in this example, the distance between a and c would be 0. Thus, not a triangle and certainly not an equilateral triangle.

Where did I go wrong here? I'm bored waiting for Calculus II in the Fall and I'm going through Courant's Differential and Integral Calculus on my free time until then (Fall term probably starting in August/September, so I'm not worried if it takes a few months to get comfortable with Courant - Calculus I has been a breeze since I already knew most of the content before taking it).

and of course:

a, b, c, d, e∈Z

Using the distance formula between each of the points and setting them equal:

\sqrt { (b - a)^2 + (e - d)^2 } = \sqrt { (c - a)^2 + (d - d)^2 } = \sqrt { (b - c)^2 + (e - d)^2 }(e+d)

^{2}= (c-a)^{2}- (b-a)^{2}(e+d)

^{2}= (c-a)^{2}- (b-c)^{2}c

^{2}- 2ac - b^{2}+2ab = -2ac + a^{2}- b^{2}+ 2bcc

^{2}+ 2ab = a^{2}+ 2bcc(c - 2b) = a(a - 2b)

Thus, for this to be true, a = c. But in this example, the distance between a and c would be 0. Thus, not a triangle and certainly not an equilateral triangle.

Where did I go wrong here? I'm bored waiting for Calculus II in the Fall and I'm going through Courant's Differential and Integral Calculus on my free time until then (Fall term probably starting in August/September, so I'm not worried if it takes a few months to get comfortable with Courant - Calculus I has been a breeze since I already knew most of the content before taking it).

Last edited: